2004
DOI: 10.1142/s0218127404009223
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a Two Degree of Freedom Vibro-Impact System With Multiple Motion Limiting Constraints

Abstract: We consider the dynamics of impact oscillators with multiple degrees of freedom subject to more than one motion limiting constraint or stop. A mathematical formulation for modelling such systems is developed using a modal approach including a modal form of the coefficient of restitution rule. The possible impact configurations for an N degree of freedom system are considered, along with definitions of the impact map for multiply constrained systems.We consider sticking motions which occur when a single mass in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…Chatter is characterized by many consecutive impacts and might therefore be exploited in triboelectric energy harvesting from vibro-impact systems. In the study of a multi-degree-of-freedom vibroimpact system, Wagg [56,61] discussed the chattering and sticking behaviour which appeared at low forcing frequencies, and showed that a variety of non-smooth events could possibly occur. Here, a numerical simulation is conducted to determine whether chatter can appear in the present system at low forcing frequencies.…”
Section: Use Of Chattermentioning
confidence: 99%
“…Chatter is characterized by many consecutive impacts and might therefore be exploited in triboelectric energy harvesting from vibro-impact systems. In the study of a multi-degree-of-freedom vibroimpact system, Wagg [56,61] discussed the chattering and sticking behaviour which appeared at low forcing frequencies, and showed that a variety of non-smooth events could possibly occur. Here, a numerical simulation is conducted to determine whether chatter can appear in the present system at low forcing frequencies.…”
Section: Use Of Chattermentioning
confidence: 99%
“…Equation (5) has the well known exact solution for under-damped oscillations 0 < ζ j < 1 [21], so that we can solve for each mode exactly, and hence find the total displacements x 1 , x 2 -see [13,22] for further details. Without loss of generality, this formulation can be considered in either a dimensional or a nondimensional form [22] -in the following work we assume all parameters and variables are nondimensional.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Without loss of generality, this formulation can be considered in either a dimensional or a nondimensional form [22] -in the following work we assume all parameters and variables are nondimensional.…”
Section: Mathematical Modelmentioning
confidence: 99%
See 2 more Smart Citations